Is Intrinsic Motivation Related to Lower Stress among University Students? Relationships between Motivation for Enrolling in a Study Program, Stress, and Coping Strategies - Sandra Schladitz; Daniel Rölle; Marie Drüge (Education Sciences, 2024)
Transitioning from high school to university can be a challenging time for students, associated with uncertainty and stress, in part resulting from the vast number of subjects to choose from. Research has shown positive associations between intrinsic motivation and student well-being. Considering the detrimental roles that students’ stress and possibly dysfunctional coping strategies can play regarding general well-being, we investigate relationships between these constructs. Motivation for enrollment in a study program was analyzed in n = 201 first- and higher-semester students with regard to different facets of motivation. Part of the freshmen sample (n = 40) completed an additional follow-up survey in their second semester, expanding on stress and coping strategies. Cross-sectional results showed different patterns of intercorrelation among the motivational facets, but no significant differences between first- and higher-semester students. Longitudinally, only motivation based on social influences decreased over the course of the first semester. Motivation did not prove to be a suitable predictor for retrospectively judged stress during the first semester, but intrinsic motivation, especially, showed encouraging connections to some coping strategies. The findings can be used to improve student well-being and reduce dropout rates, as well as to design suitable marketing strategies for universities.